Prevalence and Effects of Smartphone Addiction on Sleep Quality and Academic Performance among Male Medical Students at University of Science and Technology, Sana'a, Yemen, 2024 - Amer, Ali Mohammed; Badda, Abdullah Hassan; Badda, Yosef Hassan; Aukah, Abdulmajeed Abdullah; Abotalb, Mohammed Fouad (My University, 2024)
Background: Smartphone addiction is a growing concern worldwide and its overuse is associated with sleep disturbance among medical students. Smartphones are increasingly becoming an essential educational tool for all students and it is essential to determine the potential adverse effects. So, this study aimed to determine the prevalence and impact of smartphone addiction on Sleep Quality and Academic Performance among male Medical Students at University of Science and Technology, Sana'a, Yemen, 2024.